1999
DOI: 10.1021/jp9925886
|View full text |Cite
|
Sign up to set email alerts
|

Additivity and Transferability of Atomic Contributions to Molecular Second Dipole Hyperpolarizabilities

Abstract: Large basis set ab initio calculations of the dipole polarizabilities and second hyperpolarizabilities of a large set of organic molecules have been carried out and the results have been used to assess additivity and transferability of atomic contributions to the overall molecular response tensors. Reasonable estimates of the mean second hyperpolarizability response can be obtained from summing atomic parameters obtained here, though the reliability of the estimates is worse than what is found for dipole polar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 37 publications
1
31
1
Order By: Relevance
“…[13][14][15][16][17][18][19][20][21] Bader and co-workers 22 adopted the topological partitioning of the electron density within the Quantum Theory of Atoms in Molecules (QTAIM). The method has been successfully applied for the evaluation of intermolecular interaction energies [23][24][25] and the transferability of electrostatic properties in n-alkanes.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21] Bader and co-workers 22 adopted the topological partitioning of the electron density within the Quantum Theory of Atoms in Molecules (QTAIM). The method has been successfully applied for the evaluation of intermolecular interaction energies [23][24][25] and the transferability of electrostatic properties in n-alkanes.…”
Section: Introductionmentioning
confidence: 99%
“…Diacetylene is currently of interest due to the increasing importance of acetylenic chemistry20. Its electric properties have been studied at various levels of theory21–24. Several experimental studies of the hyperpolarizability of diacetylene derivatives have been reported recently25–27.…”
Section: Introductionmentioning
confidence: 99%
“…These high‐level ab initio determinations contribute also to building a database that will be used for estimating the hyperpolarizabilities of unknown compounds within approximate models such as the bond or atom additivity schemes. Such bond/atom characteristics have already been obtained for the electronic hyperpolarizabilities either from theoretical or THG experimental 38, 39 investigations.…”
Section: Discussionmentioning
confidence: 83%